2016
DOI: 10.1093/bja/aew099
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic efficacy of local infiltration analgesia vs femoral nerve block after total knee arthroplasty: a systematic review and meta-analysis

Abstract: Many consider femoral nerve block the gold standard in pain management following knee arthroplasty. Local infiltration analgesia is an alternate approach that applies the concept of surgical wound infiltration with local anaesthetics. This meta-analysis aims to compare both analgesic treatments for analgesia and functional outcomes after total knee arthroplasty. This meta-analysis was performed according to the PRISMA statement guidelines. The primary outcomes were cumulative i.v. morphine consumption, pain sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
0
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 53 publications
6
73
0
8
Order By: Relevance
“…This highlights the often under-appreciated role of local infiltration analgesia (LIA) in the management of early post-operative pain. In 2016 Albrecht et al [3] published a meta-analysis of 1,112 patients sourced from fourteen randomised controlled trials, comparing LIA with femoral nerve block (FNB) in total knee arthroplasty (TKA) [3]. This study showed LIA to be equivalent to FNB in regard to 24 hour post-operative pain scores, morphine consumption and complications such as infection and falls.…”
Section: Commentarymentioning
confidence: 99%
“…This highlights the often under-appreciated role of local infiltration analgesia (LIA) in the management of early post-operative pain. In 2016 Albrecht et al [3] published a meta-analysis of 1,112 patients sourced from fourteen randomised controlled trials, comparing LIA with femoral nerve block (FNB) in total knee arthroplasty (TKA) [3]. This study showed LIA to be equivalent to FNB in regard to 24 hour post-operative pain scores, morphine consumption and complications such as infection and falls.…”
Section: Commentarymentioning
confidence: 99%
“…This surgery is mostly associated with moderate to severe pain [1,2]. Good post-operative analgesia after TKR facilitates of early mobilization, reduction of length of hospital stay, less postoperative complications, prevents progression of acute pain to chronic pain and provides a hemodynamic stability [3].…”
Section: Introductionmentioning
confidence: 99%
“…LAI usually administrates as periarticular or with intra-articular infiltration. Meanwhile, the efficacy of LAI was comparable to that of epidural anesthesia, femoral nerve block (FNB) [2], adductor canal block (ACB) [5], and intrathecal morphine [6]. Sciatic nerve block (SNB) and LAI are two major options to supplement FNB in relieving of pain after TKR, However, its short duration of action limited its clinical application [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was reported that PAI might be better than continuous femoral nerve block in terms of pain relief after TKA in retrospective [17,23] and prospective trials [12,19], and might even improve the time for discharge from the hospital [9]. One recent meta-analysis of 14 randomized controlled trials confirmed that femoral nerve block was not superior to PAI in terms of opioid consumption, pain scores (at rest or movement), ROM, muscle strength and length of stay [1]. Continuous PAI was also reported to be equivalent to continuous femoral nerve block in terms of analgesic profiles after TKA [21], or even better and allowed for better function and less risk of motor weakness [18].…”
mentioning
confidence: 99%